HUBUNGAN KECANDUAN GAMES ONLINE TERHADAP PERKEMBANGAN PSIKOSOSIAL ANAK USIA SEKOLAH DASAR - Emmelia Christin Simatupang; Sri Wahyuni; Hellena Deli (Fakultas Keperawatan, Universitas Riau, 2023)
Online games are online games that are played on computers, smartphones and other gaming devices. One of the users is school-aged children. Addiction to games in school children is characterized by playing outside the allotted time which has a negative impact on their psychosocial development. The purpose of this study was to determine the relationship between internet gaming and the psychosocial development of elementary school students. Descriptive correlation with a cross-sectional approach is used as a research method. In this study there were 65 respondents who were selected based on inclusion criteria using a stratified random sampling technique. The measuring tool used is a questionnaire that has been modified by the researcher. The results showed that most of the respondents were 11 years old (47.7%) and male (60.0%). The average time to play games is not more than 1-3 hours/day (67.7%), most of the respondents are identified as addicted to online games (67.7%) and have adequate psychosocial development (58.5%). Analysis using Fisher's exact test shows that p-value (0.00) < α (0.05) means that there is a relationship between online games and the psychosocial development of school-age children. Parents and teachers are encouraged to work closely with the health care team to identify a child's play disorder that affects psychosocial development